Exploring Women's Reasons for Choosing Home Birth with the Help of Their Untrained Family Members: A Qualitative Research - Nila Kusumawati; Erlinawati Erlinawati; Yenny Safitri; Muhammad Nurman; Fitry Erlin (Shiraz University of Medical Sciences, 2023)
Background: Home births with the help of untrained family members continue to be women'spreference in Indonesia. However, the practice has received very little attention. The purpose of thisstudy was to explore women's reasons for choosing home births with the help of their untrained familymembers.Methods: This study used an exploratory-descriptive qualitative research approach and was conductedfrom April 2020 to March 2021 in Riau Province, Indonesia. A total of 22 respondents determined bydata saturation was recruited using purposive and snowball samplings. The respondents consisted of12 women who had at least one planned home birth with the help of their untrained family members,and 10 untrained relatives who had an experience in intentionally assisting their family member's homebirth. Data were collected through semi-structured telephone interviews. Nvivo version 11 softwarewas used for data analysis using the Graneheim and Lundman's content analysis.Results: 13 categories and 4 themes emerged. The themes were living with fallacious beliefs inunassisted home childbirths, feeling of socially alienated from the surrounding communities, dealingwith limited access to healthcare services, and escaping from childbirth-related stressors.Conclusion: Home birth with the help of untrained family members takes place because of not onlylimited access to healthcare services, but also women's personal beliefs, values, and needs. Designingculturally sensitive health education, ensuring culturally competent healthcare workers and services,overcoming healthcare access barriers, and improving the community's pregnancy and childbirthliteracies are fundamental in reducing unassisted home births and promoting facility childbirths.